Tembang Dolanan Sebagai Media Pembelajaran PAI dalam Membangkitkan Nilai Religius Peserta Didik - Wahyudi, Dedi; Azhar, Azhar (Tarbawiyah Jurnal Ilmiah Pendidikan, 2023)
Education must integrate spiritual and cultural excellence, one of which is by using the media tembang dolanan. Cultural products such as traditional songs can be used as learning media that are infused with religious character values and virtues. One of these songs is Sluku-Sluku Bathok. Sluku-sluku bathok has a rich meaning that the creator wants to convey to the people who hear it. After an in-depth analysis of the song Sluku-Sluku Bathok has religious values that include the dimensions of faith, worship, and morals contained in each lyric. To instil Islamic values based on local wisdom in education, strong support is needed from institutions that care about the importance of these religious values. The school curriculum that has been prepared and implemented well shows that the institution has provided strong support in realising this hope. The approach used to instil local wisdom-based Islamic values to students is to cultivate religious values based on local wisdom, one of which is using this dolanan song. The role playing model is one of the models to implement the Sluku-Sluku Bathok song in PAI learning methodology so that it can internalise religious values.